Minitomateiro em sistema orgânico inoculado com Trichoderma asperellum e consorciado com hortaliças da família fabaceae - Corsini, Igor (2020)
The inoculation of the beneficial soil fungus Trichoderma asperellum and the intercropped crop cultivation has presented advantages that constitute interesting strategies for family farming and organic production systems. The objective of this study was to evaluate the production performance of the minitomate inoculated with T. asperellum and intercropped with the fabaceous vegetables. The experimental design was in randomized blocks, with and without T. asperellum application in the consortiums of mini tomato with chickpeas (Cicer arietinum), white lupine (Lupinus albus), snow pea (Pisum sativum var. saccharatum) and single cultivation (control), with four repetitions. Were evaluated: production of fresh and dry mass of fabaceous; chlorophyll content of mini tomatoes; yield, physicochemical parameters of fruits and sensory analysis of mini tomatoes. The efficient land use index (ELU) was also determined. The intercropping with lupine showed lower production of fresh and dry mass of mini tomatoes, however, showed higher ELU when compared to monoculture cultivation. The productivity of the intercropping with chickpea and pea did not differ from the control, but these fabaceae did not adapt well to the conditions of the experiment. The inoculation of T. asperellum in the soil increased the productivity of the mini tomato over time, independently of the intercropping, becoming a promising technique for family farming and organic production.